Regression of Post-orthodontic Lesions by a Remineralizing Cream - Bailey, D.L.; Adams, G.G.; Tsao, C.E.; Hyslop, A.; Escobar, K.; Manton, D. J.; Reynolds, E.C.; Morgan, M.V. (Journal of dental research, 2009)
Orthodontic patients have an increased risk of white-spot lesion formation. A clinical trial was conducted to test whether, in a post-orthodontic population using fluoride toothpastes and receiving supervised fluoride mouthrinses, more lesions would regress in participants using a remineralizing cream containing casein phosphopeptide- amorphous calcium phosphate compared with a placebo. Forty-five participants (aged 12–18 yrs) with 408 white-spot lesions were recruited, with 23 participants randomized to the remineralizing cream and 22 to the placebo. Product was applied twice daily after fluoride toothpaste use for 12 weeks. Clinical assessments were performed according to ICDAS II criteria. Transitions between examinations were coded as progressing, regressing, or stable. Ninety-two percent of lesions were assessed as code 2 or 3. For these lesions, 31% more had regressed with the remineralizing cream than with the placebo (OR = 2.3, P = 0.04) at 12 weeks. Significantly more post-orthodontic white-spot lesions regressed with the remineralizing cream compared with a placebo over 12 weeks.